El género como herramienta crítica desde la Teoría crítica inmanente de Rahel Jaeggi - Falcon Valdivia, Valeria (2023)
The overall goal of this paper is to approach the concept of gender from the perspective of the immanent critique proposed by Rahel Jaeggi while also considering some of the contributions made by Sally Haslanger regarding the challenges and tasks of Critical Theory. I argue immanent critique to be a solid methodological proposal that allows to address and clarify social pathologies in the contemporary context. To this end, I bring the methodology and normative considerations of immanent critique into dialogue with the anthropological analysis of the concept of gender from the works of Joan Scott and Marta Lamas.